More to love : the art of living together. - Curtin, Brian; Nitpolprasert, Chattiya; Bangkok; Chiang Mai (Barcelona : ARTAIDS Barcelona, 2008)
Cooper, Emmanuel ; Crimp, Douglas ; Indiana, Gary ; Jarman, Derek ; Klein-Davis, Jennie ; Kotz, Liz ; Miller, D.A. ; Chua, Lawrence ; Takemoto, Tina ; Watney, Simon ; Chusuwan, Amrit ; Rungjang, Arin ; Weiss, Erich ; Kaap, Gerald Van Der ; Phaosavasdi, Kamol ; Ngamsom, Krit ; Copers, Leo ; Sriwanichpoom, Manit ; Oranniwesna, Nipan ; Thammarak, Noree ; Nuts Society and Practical Studio ; Berchem, Otto ; Chychookiat, Patiroop ; Yamazaki, Pornprasert ; Phinthong, Pratchaya ; Suthathongthai, Prateep ; Kunavichayanont, Sutee ; Cooper, Tintin ; Guptabutra, Toeingam ; Changtrakul, Top
Biog. per kunstenaar
Engels
Published on the occasion of the exhibition "More to love: the art of living together" in Bangkok, 24.07.2008 - 15.08.2008 and in Chiang Mai, 28.11.2008 - 19.12.2008
boek